The Fusaric Acid Derivative qy17 Inhibits Staphylococcus haemolyticus by Disrupting Biofilm Formation and the Stress Response via Altered Gene Expression - Wang, Bing; Song, Chao-Rong; Zhang, Qing-Yan; Wei, Peng-Wei; Wang, Xu; Long, Yao-Hang; Yang, Yong-Xin; Liao, Shang-Gao; Liu, Hong-Mei; Xu, Guo-Bo (Frontiers in Microbiology, 2022)
Staphylococcus haemolyticus (S. haemolyticus) is the second most commonly isolated coagulase-negative staphylococcus (CoNS) in patients with hospital-acquired infections. It can produce phenol-soluble modulin (PSM) toxins and form biofilms. Compared with the wealth of information on Staphylococcus aureus and Staphylococcus epidermidis, very little is known about S. haemolyticus. There is an urgent need to find an effective preparation to combat the harm caused by S. haemolyticus infection. Chinese herbs have been utilized to cure inflammation and infectious diseases and have a long history of anticancer function in China. Here, we modified fusaric acid characterized from the metabolites of Gibberella intermedia, an endophyte previously isolated from Polygonum capitatum. This study shows that fusaric acid analogs (qy17 and qy20) have strong antibacterial activity against S. haemolyticus. In addition, crystal violet analyses and scanning electron microscopy observations demonstrated that qy17 inhibited biofilm formation and disrupted mature biofilms of S. haemolyticus in a dose-dependent manner. Additionally, it reduced the number of live bacteria inside the biofilm. Furthermore, the antibiofilm function of qy17 was achieved by downregulating transcription factors (sigB), transpeptidase genes (srtA), and bacterial surface proteins (ebp, fbp) and upregulating biofilm-related genes and the density-sensing system (agrB). To further elucidate the bacteriostatic mechanism, transcriptomic analysis was carried out. The following antibacterial mechanisms were uncovered: (i) the inhibition of heat shock (clpB, groES, groL, grpE, dnaK, dnaJ)-, oxidative stress (aphC)- and biotin response (bioB)-related gene expression, which resulted in S. haemolyticus being unable to compensate for various stress conditions, thereby affecting bacterial growth; and (ii) a reduction in the expression of PSM-beta (PSMβ1, PSMβ2, PSMβ3) toxin- and Clp protease (clpP, clpX)-related genes. These findings could have major implications for the treatment of diseases caused by S. haemolyticus infections. Our research reveals for the first time that fusaric acid derivatives inhibit the expression of biofilm formation-related effector and virulence genes of S. haemolyticus. These findings provide new potential drug candidates for hospital-acquired infections caused by S. haemolyticus.